Advances in Intelligent Systems and Computing Selected Papers from the International Conference on Computer Science and Information Technologies, CSIT 2016, September 6-10 Lviv, Ukraine - Shakhovska, Natalya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book reports on new theories and applications in the field of intelligent systems and computing. It covers computational and artificial intelligence methods, as well as advances in computer vision, current issue in big data and cloud computing, computation linguistics, cyber-physical systems as well as topics in intelligent information management. Written by active researchers, the different chapters are based on contributions presented at the workshop in intelligent systems and computing (ISC), held during CSIT 2016, September 6-9, and jointly organized by the Lviv Polytechnic National University, Ukraine, the Kharkiv National University of RadioElectronics, Ukraine, and the Technical University of Lodz, Poland, under patronage of Ministry of Education and Science of Ukraine. All in all, the book provides academics and professionals with extensive information and a timely snapshot of the field of intelligent systems, and it is expected to foster new discussions andcollaborations among different groups. .
An Improved Particle Swarm Optimization Algorithm with Repair Procedure.-Fuzzy Evaluation Method for Project Profitability -- New approach for Saving Semistructured Medical Data -- Architecture and Conceptual Bases of Cloud IT Infrastructure Managemen -- Generation of the Association Rules Among Multidi-mensional Data in DBMS Caché Environment -- Threat Assesment Method For Intelligent Disaster Decision Support SysteM -- Mobile Activation Learning System Using Gamification Approach -- University's Information Image as a Result of University Web Communities' Activities -- Multi-Modular Optimum Coding Systems Based on Remarkable Geometric Properties of Space -- The Method of Statistical Analysis of the Scientific, Colloquial, Belles-Lettres and Newspaper Styles on the Phonological Level -- Theoptimal Aggregation of Integrated Regional Systems "Production, Wasterecycling" -- Intelligent Systems Designof Distance Learning Realization for Modern Youth Promotion and Involvement in Independent Scientific Researches -- An Ontology-based Approach for User Interface Adaptation -- Algebraic Framework for Knowledge Processing in Systems With Situational Awareness -- Classification Methods of Text Documents Using Ontology Based Approach -- The Identıfıcatıon of the Operator's Systems Images Usıng the Method of the Phase Portraıt -- Concept implementation of Decision Support Software for the Risk Management of Complex Technical System -- The Model of Data Analysis of the Psychophysiological Survey Results -- Two Algorithms Median Filtering to Identify the Time Series Trend -- Use Electric and Acoustic Technologies for Automated Control of Water -- Analysis of Clustering Algorithms -- Semantic Search Personalized Data as Special Method of Processing Medical Information.
Keywords: Computational intelligence; Data mining; Telecommunication; Business information services; Artificial intelligence; Computational Intelligence; Data Mining and Knowledge Discovery; Communications Engineering, Networks; IT in Business; Artificial Intelligence